2014
DOI: 10.1155/2014/508185
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization Design of Double-Row Blades Hydraulic Retarder with Surrogate Model

Abstract: For the design of double-row blades hydraulic retarder involves too many parameters, the solution process of the optimal parameter combination is characterized by the large calculation load, the long calculation time, and the high cost. In this paper, we proposed a multiobjective optimization method to obtain the optimal balanced solution between the braking torque and volume of double-row blades hydraulic retarder. Moreover, we established the surrogate model for objective function with radial basis function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The basic performance requirements of hydrodynamic retarders are good braking performance at low speeds, a quick response system, smooth braking torque, and good thermal decay performance [18]. To propose the criteria from multiple angles, a detailed literature search focusing on concepts related to braking performance evaluation was conducted.…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…The basic performance requirements of hydrodynamic retarders are good braking performance at low speeds, a quick response system, smooth braking torque, and good thermal decay performance [18]. To propose the criteria from multiple angles, a detailed literature search focusing on concepts related to braking performance evaluation was conducted.…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…A hydraulic retarder is a typical rotor-stator fluid machinery, which consists of a pump (rotor) and a turbine (stator). Lately, the reported studies involving hydraulic retarders still indicated that RANS, such as standard k-ε (Chen et al , 2016; Chunbao et al , 2015), realizable k – ε (Chunbao et al , 2015), renormalization-group k – ε (Liu et al , 2015b) and SST(Mu et al , 2016), played an important role in its internal flow calculation. RANS simulations resulted in failures in rotor-stator fluid machinery applications, particularly those that involved strong curvature, rapid compression or expansion and a strong swirl (Argyropoulos and Markatos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic retarders (HRs) are auxiliary braking devices of vehicles that can reduce vehicle speed by converting the kinetic energy of vehicle to thermal energy of working fluid. 1,2 Instead of service braking, HR can be used to regulate vehicle speed effectively under nonemergency braking conditions. Compared with other auxiliary braking devices, HR has the advantages of high braking power, durable efficiency, and zero pollution.…”
Section: Introductionmentioning
confidence: 99%